2021
DOI: 10.1126/sciadv.abj1398
|View full text |Cite
|
Sign up to set email alerts
|

Honey bees increase social distancing when facing the ectoparasite Varroa destructor

Abstract: Honey bees modify their social organization to hinder the spread of parasites within the colony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…In contrast, post-introduction populations are much more dispersed across the landscape (Fig. 3B), reflecting movement strategies which lead to near-perpetual movement to avoid associations; a sort of dynamic social distancing (Pusceddu et al, 2021). This dispersed population structure means that most foragers encounter fewer than 10% of the population over their lifetime (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, post-introduction populations are much more dispersed across the landscape (Fig. 3B), reflecting movement strategies which lead to near-perpetual movement to avoid associations; a sort of dynamic social distancing (Pusceddu et al, 2021). This dispersed population structure means that most foragers encounter fewer than 10% of the population over their lifetime (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This change actually occurs over fewer generations than over which key aspects of animal culture and ecology, such as migration routes, are established through social learning (Jesmer et al, 2018; Cantor et al, 2021 b ). Current and expected cross-species transmissions of novel pathogens (Carlson et al, 2021; Pusceddu et al, 2021) should thus prompt concern that the evolutionary consequences of pathogen introduction could slow the transmission of, and erode, animal culture (Cantor et al, 2021 b ).…”
Section: Discussionmentioning
confidence: 99%
“…Such approaches facilitated the quantification of unintended effects mediated by agricultural pesticides (e.g., a commercial formulation containing the synthetic fungicides chlorothalonil and thiophanate-methyl) in A. mellifera colonies. Colonies that received pesticide sublethallytreated bees exhibited higher mortality levels, had lower swarm entropy and energy levels, and anticipated the collective activities for the peripheral hive areas, indicating a behavioral change possibly related to physiological alteration, which is suggested as a social behavioral strategy in honey bees [51,52].…”
Section: Discussionmentioning
confidence: 98%
“…In general, sublethal doses of pesticides in bees can act as physiological stressors, altering metabolic responses (e.g., oxidative stress), glandular (e.g., hypopharyngeal, fat body), and bee brain (e.g., JH, biogenic amines), which alter their behavior and decrease longevity [52]. On the other hand, the distancing behavior has a social character, in which the contaminated worker bees distance themselves from the brood area, representing the most susceptible individuals in the colony, migrating earlier than expected to the peripheral areas of the comb [59,60], thus preserving colony health [52]. Despite fungicides seeming to represent lower acute toxicity, recent studies have shown their abilities to unbalance bee health by modifying quercetin-dependent detoxification [57,58,61], which can detrimentally affect mitochondrial regeneration and ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Humans are known for their capacity to isolate bearers of new pathogens. Strategies to reduce the contact between healthy and possibly infected individuals were recently observed in honey bees (Pusceddu et al, 2021 ). Even slime mould avoids conspecifics that face increased levels of (both biotic and abiotic) stress (Briard et al, 2020 ).…”
mentioning
confidence: 99%